Fluorescence behavior of isoflavones: pH-dependent effects - Lvovska, M.I.; Roshal, A.D.; Doroshenko, A.O.; Kyrychenko, A.V.; Khilya, V.P. (Functional Materials, 2005)
Fluorescence spectra of isoflavones are studied in the pН/Н₀ range 12 to -10. The assignment of the observed emission bands to acid-base forms of isoflavones is done, the pН/Н₀ ranges of the existence of each of forms are determined. In 7-methoxyisoflavone solutions, only fluorescence of the cationic form is detected. In the case of 7-hydroxyisoflavones, the fluorescence of the cationic, anionic and phototautomeric forms are found. The emission band in the range 400-420 nm characteristic for all isoflavones is assigned to their photodestruction products. The dissociation and protonation constants of isoflavones in the ground and excited states are evaluated. Изучены спектры флуоресценции изофлавонов в интервале рН/Н₀ от 12 до -10. Проведено отнесение наблюдаемых полос испускания к кислотно-основным формам изофлавонов в возбужденном состоянии, определены интервалы рН/Н₀ существования каждой из форм. В растворах 7-метоксиизофлавонов обнаружена флуоресценция только катионной формы. В случае 7-гидроксиизофлавонов обнаружена флуоресценция катионной, анионной и фототаутомерной форм. Полоса испускания в области 400-420 нм, характерная для всех изофлавонов, отнесена к продуктам их фотораспада. Рассчитаны константы диссоциации и протонирования изофлавонов в основном и возбужденном состояниях. Дослiджено спектри флуоресценцiї iзофлавонiв в iнтервалi рН/Н₀ вiд 12 до -10. Проведено вiднесення смуг випромiнення, що спостерiгаються, до кислотно-основних форм iзофлавонiв у збудженому станi, визначено iнтервали рН/Н₀ iснування кожної з форм у розчинах. В розчинах 7-метоксиiзофлавонiв знайдено флуоресценцiю тiльки однiєї - катiонної форми. Для 7-гiдроксиiзофлавонiв зареєстровано флуоресценцiю катiонної, анiонної та фототаутомерної форм. Смуга випромiнення в областi 400-420 нм, що є характерною для всiх iзофлавонiв, вiднесена до продуктiв їх фоторозкладу. Розраховано константи дисоцiацiї та протонування iзофлавонiв в основному та збудженому станах.